Activity Intervention in COPD Patients to Improve Quality of Life in The Comunity - Iwan Shalahuddin; Bambang Aditya Nugraha; Sandra Pebrianti; Theresia Eriyani; Devi Nurrahmawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The problem that often arises in chronic diseases such as COPD is shortness of breath (dyspnea), which causes the patient to experience activity intolerance. Activity intolerance is characterized by a decrease in the patient's ability to carry out physical activities or work that is quite heavy. This Literature Review report aims to find out what activity-based interventions have been shown to improve the quality of life of COPD patients significantly and can be implemented in the community. The author uses the method used to conduct a literature review is to search through the internet. Search literature through the internet based on several criteria, namely journals published in the last 10 years, English-language research types in the form of Randomized Control trials, and Quasi-Experimental. The keywords used are ((COPD) or (chronic obstructive pulmonary disease) or (chronic obstructive airway disease) or (chronic obstructive lung disease)) AND ((activity exercise) or (exercise intervention)) AND (quality of life) or (well-being) or (well-being) or (health-related quality of life) or (life satisfaction)) AND (RCT) or (Quasi-Experimental) through NCBI and Ebsco. From the nine articles, it was found that there were 8 interventions related to improving the quality of life of the elderly with COPD. Based on the elements that were proven to be significant, there was 1 intervention with p = 0.000 related to improving quality of life, the intervention was upper extremity resistance training. Intervention activities in COPD patients to improve quality of life, each intervention group has the most effective intervention significant influence. So that the semi-Fowler's position is very effective in increasing extremity muscle strength in COPD patients with activity intolerance problems Abstrak: Permasalahan yang sering muncul pada penyakit kronis seperti PPOK adalah sesak nafas (dyspnea), yang menyebabkan pasien mengalami intoleransi aktivitas. Intoleransi aktivitas ditandai dengan adanya penurunan kemampuan pasien dalam melakukan aktivitas fisik atau pekerjaan yang cukup berat. Laporan Literatur Review ini bertujuan untuk mengetahui intervensi berbasis aktivitas apa yang terbukti signifikan dapat meningkatkan kualitas hidup pasien PPOK dan dapat diimplementasikan pada komunitas. Penulis menggunakan metode yang digunakan untuk melakukan tinjauan pustaka adalah dengan pencarian melalui internet. Pencarian literatur melalui internet berdasarkan beberapa kriteria yaitu jurnal dipublikasikan pada 10 tahun terakhir, berbahasa inggris jenis penelitian berupa Randomized Control Trial dan Quasi Experimental. Kata kunci yang digunakan yaitu ((copd) or (chronic obstructive pulmonary disease) or (chronic obstructive airway disease) or (chronic obstructive lung disease)) AND ((activity exercise) or (exercise intervention)) AND ((quality of life) or (well being) or (well-being) or (health-related quality of life) or (life satisfaction)) AND (RCT) or (Quasi Experimental) melalui NCBI dan Ebsco. Dari 9 Jurnal tersebut, didapatkan bahwa ada 8 intervensi yang berkaitan dengan peningkatan kualitas hidup lansia dengan PPOK. Berdasarkan elemen yang terbukti signifikan terdapat 1 intervensi dengan p = 0.000 terkait peningkatan kualitas hidup, intervensi tersebut yaitu latihan ketahanan ekstremitas atas. Intervensi aktivitas pada pasien PPOK untuk meningkatkan kualitas hidup, masing-masing kelompok intervensi memiliki intervensi yang paling efektif berpengaruh secara signifikan. Sehingga tindakan posisi semi fowler sangat efektif dalam meningkatkan kekuatan otot ekstermitas pada pasien PPOK dengan masalah intoleransi aktivitas